Navigating the intermestic nexus: Strategic agency and multidimensional security in Indonesia’s transition to the new order, 1966 to 1967 - Mohammad Rikaz Prabowo; Sudagung, Adityo Darmawan Sudagung; Nurhadianto, Nurhadianto (Program Pascasarjana Universitas Negeri Yogyakarta, 2026)
This article explores the connections between the transition of the Indonesian regime, international diplomacy, and domestic economic development during the years 1966 to 1967. Utilizing a historical methodology that includes heuristics, source criticism, interpretation, and historiography, the study examines primary data from the Angkatan Bersendjata newspaper alongside contemporary archival literature to clarify how Suharto's administration redefined national threats. The research argues that Suharto's actions inferred an intermestic logic, where the prioritisation of domestic stability served as a foundation for normalising foreign relations. By analysing Suharto’s leadership and strategic motives, the article shows a significant shift in Indonesia’s perception of threats, moving from external confrontation to internal consolidation. This study contributes to both historiography and International Relations by framing the interregnum of 1966 to 1967 as a period of intentional and multifaceted statecraft. By articulating the intersection of economic rehabilitation and security policy, the article also adds to existing scholarship, asserting that the transition from the Old Order to the New Order was facilitated by a well-integrated balancing of the state's economy, foreign affairs, and national security.